The effects of social support and coping strategies on academic stress among final-year college students - Dhiya Alya Yunizar; Desi Maulia; Eka Sari Setianingsih (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Grounded in the transactional model of stress and the stress-buffering hypothesis, this study examined the predictive roles of social support and coping strategies on academic stress among final-year counseling students. This population represents prospective counseling professionals who simultaneously face academic completion demands and professional competency requirements, a group that remains underrepresented in academic stress research. Using a quantitative correlational design, data were collected from 98 eighth-semester Guidance and Counseling students at Universitas PGRI Semarang selected through proportional random sampling from a population of 130 students. Sample adequacy was supported by the Slovin formula and a priori power analysis. Instruments included the Social Support Scale (α = .981), Ways of Coping Questionnaire (α = .940), and Student-Life Stress Inventory (α = .944). Multiple regression analysis indicated that social support (t = −8.832, p < .001) and coping strategies (t = −9.129, p < .001) significantly and negatively predicted academic stress. Together, both variables explained 63.1% of the variance in academic stress (R² = .631, p < .001). Findings support the stress-buffering hypothesis and the transactional model of stress, suggesting that higher levels of social support and more adaptive coping strategies are associated with lower academic stress. However, causal conclusions are limited by the cross-sectional design.